The type specimens, type localities and nomenclature of Sarcoramphus vultures (Aves: Cathartidae), with a note on their speciation - Mlíkovský, Jiří (Zootaxa, 2015)
A nomenclatural review of Sarcoramphus vultures resulted in the following: The genus Sarcoramphus was described by Duméril in 1805 rather than 1806. Vultur papa Linnaeus, 1758, is the type of Sarcoramphus by subsequent monotypy (Froriep in Duméril 1806), not by Vigors's (1825) designation. The type of the genus Gypagus Vieillot, 1816, is, by monotypy, Vultur gryphus Linnaeus, 1758, not Vultur papa Linnaeus, 1758. Due to this, Gypagus is a junior objective synonym of Vultur Linnaeus, 1758. Gyparchus was created by Gloger (1841) as a new genus for Vultur papa Linnaeus, 1758, not as an emendation of Gypagus Vieillot, 1816. Vultur papa Linnaeus, 1758 was found to be possibly based on syntypes from two different taxa and a lectotype is here designated. The author of Vultur sacer is Zimmermann (in Bartram 1793), not Cassin (1853). Possible speciation events in the genus Sarcoramphus are also discussed.